2002
DOI: 10.1128/jb.184.11.3130-3134.2002
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a cheA Mutant of Treponema denticola

Abstract: The Treponema denticola cheA gene, encoding the central kinase of the general chemotaxis pathway, was analyzed for its role in chemotaxis and tissue penetration. The cheA gene was interrupted by insertion of an ermF-ermAM gene cassette. Reverse transcription-PCR confirmed that the other downstream chemotaxis genes within the same operon (cheW, cheX, and cheY) were still expressed in the cheA mutant strain. Lack of cheA resulted in decreased swarming on soft-agar swarm plates and failure to respond chemotactica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Allelic replacement mutagenesis of two MCP encoding genes, dmcA and dmcB, resulted in a decreased chemotactic response to serum and albumin (Kataoka et al, 1997;Li et al, 1999). As expected, a cheA knockout mutant, which lacks the central kinase of the chemotaxis pathway, failed to respond chemotactically to serum (Lux et al, 2002).…”
Section: Chemotaxissupporting
confidence: 79%
“…Allelic replacement mutagenesis of two MCP encoding genes, dmcA and dmcB, resulted in a decreased chemotactic response to serum and albumin (Kataoka et al, 1997;Li et al, 1999). As expected, a cheA knockout mutant, which lacks the central kinase of the chemotaxis pathway, failed to respond chemotactically to serum (Lux et al, 2002).…”
Section: Chemotaxissupporting
confidence: 79%
“…Because the treponemes have only one homolog of these genes in their genomes, these clusters also likely function in chemotaxis. In support of this proposition, analysis of a cheA mutant in T. denticola revealed it to be nonchemotactic (37 Reactions were stopped, and products were analyzed as described in the text. Phosphor images are shown in the left panels, and relative intensities (PI "volumes") are shown in the right panels.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies have shown that CheW 3 is essential for both chemotaxis and the polar clustering of the MCPs (28). The C terminus of CheW 3 contains a CheRlike domain, a combination that is found only in some spirochete species (28,55). It is likely that this unique domain architecture may require an additional partner, such as BB0569, to facilitate its physical interactions with the MCPs.…”
Section: Discussionmentioning
confidence: 99%